Using historical maps to analyze two hundred years of land cover changes: case study of Sorrento peninsula (south Italy). Issue 3 (26th May 2016) - Pindozzi, Stefania; Cervelli, Elena; Capolupo, Alessandra; Okello, Collins; Boccia, Lorenzo
ABSTRACT: Historical maps are effective sources of geographical information and useful for historical and territorial research. In this study, the examination of landscape dynamics on the basis of historical maps over a period of more than 200 years was conducted. The study area is Sorrento peninsula and part of the near Sarno river basin in South Italy. This study provides a general framework for the assessment of the overall quality and accuracy of historical maps. The application of the methodology used in this specific case study can contribute to a better understanding of the dynamics of the landscape in the long term. The derived knowledge can be applied in the planning of the landscape in order to implement correct conservation strategies. The comparison was made on four maps 1817, 1875, 1960, and 2006. Geodetic accuracy of the sheet maps of 1817 and 1875 offer a right basis for a macro analysis of land cover dynamics, evaluating conversion from one land cover category to another. Main transformation, identified in the period between 1875 and 1960, was the disappearance of vineyards, which covered 25% of the total study area in 1875. Agricultural areas increased in this period to cover 57% of the total area.